2021
DOI: 10.1016/j.ebiom.2021.103551
|View full text |Cite
|
Sign up to set email alerts
|

IBD metabonomics predicts phenotype, disease course, and treatment response

Abstract: Metabonomics in inflammatory bowel disease (IBD) characterizes the effector molecules of biological systems and thus aims to describe the molecular phenotype, generate insight into the pathology, and predict disease course and response to treatment. Nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry (MS), and integrated NMR and MS platforms coupled with multivariate analyses have been applied to create such metabolic profiles. Recent advances have identified quiescent ulcerative colitis as a dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Dysbiosis is a known phenomenon in IBD, which influences the host metabolome. 30 Both dysbiosis and inflammation in IBD alter the regulation of several metabolic pathways like amino acids, SCFAs, lipids, BAs, carbohydrates, proteins, and others. These changes have been associated with IBD pathogenesis.…”
Section: Metabolome In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Dysbiosis is a known phenomenon in IBD, which influences the host metabolome. 30 Both dysbiosis and inflammation in IBD alter the regulation of several metabolic pathways like amino acids, SCFAs, lipids, BAs, carbohydrates, proteins, and others. These changes have been associated with IBD pathogenesis.…”
Section: Metabolome In Inflammatory Bowel Diseasementioning
confidence: 99%
“… 33 Low plasma histidine level has also been suggested to be associated with poorer disease course. 34 36 …”
Section: Stratifying Ibd Patients At Diagnosis: Predictors Of Disease...mentioning
confidence: 99%
“…Metabolomics could also help in predicting the response to biotherapies. 36 In a prospective longitudinal cohort study enrolling 76 CD patients, Ding et al 264 demonstrated that a range of metabolic biomarkers may contribute to prediction of response to anti-TNF therapy in CD patients. Primary non-responders tended to have modification of serum lipids (higher level of ceramide and sphingomyelin) as well as serum and faecal bile acids changes (higher levels of circulating primary unconjugated bile acids as well as higher levels of bile acids conjugated to sulphate, taurine and glycine in faeces).…”
Section: Choosing the Appropriate Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, metabolites participate in the pathogenesis of multiple diseases by acting as signaling molecules, immune modulators, endogenous toxins, and environmental sensors 10 . In particular, changes in tricarboxylic acid cycle intermediates, amino acid and lipid metabolism products, as well as oxidative metabolites are closely associated with energy metabolism, intestinal barrier, immune system, and disease activity in patients with IBD [13][14][15] . Additionally, emerging evidence suggests that alterations in metabolism are not only a feature of brosis but may also play an in uential role in its pathogenesis [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%